Effects of bacterial dextran on soil geophysical properties. Issue 2 (20th April 2017) - Ta, Hien Xuan; Muhunthan, Balasingam; Ramezanian, Somayeh; Abu-Lail, Nehal; Kwon, Tae-Hyuk
Abstract : Leuconostoc mesenteroides is a model bacterium capable of producing a viscous polysaccharide, dextran, when supplied with sucrose. When L. mesenteroides bacteria are grown in soil, the accumulation of dextran has profound effects on the physical and transport properties of soils. This study examines the feasibility of using P-wave and S-wave signatures to monitor the accumulation of dextran in sand and its consequential effects on bioclogging in sands. To achieve this goal, a column experiment stimulating the production of dextran by L. mesenteroides was performed along with monitoring of changes in permeability, responses of P- and S-wave transmission and electrical resistivity. After 41 d, scanning electron microscopy images of the tested sand showed a notable amount of dextran accumulated in the pore space as well as coating the sand grains. The results show that permeability was reduced by more than one order of magnitude, the attenuation factor characteristics of the soils were increased and electrical resistivity increased. However, minimal changes in the P- and S-wave velocities were observed, indicating that dextran production has little effect on soil stiffness.